(untitled) - Kodama, Fumio (Boston, 1995)
For managers seeking to understand how Japan has sustained a premier position in high-technology industries, Fumio Kodama provides a model that sheds light on global technology competition. He examines the technology strategies of large Japanese firms, arguing that a new paradigm shift favors their strengths in demand articulation and technology fusion. Using rigorous scientific measurement, historical perspective, and in-depth case studies, he presents an analysis from which companies--and governments--can draw enduring lessons. Analyzing data gathered over ten years of intensive research and study of Japanese firms, he distinguishes six dimensions along which the paradigm shift is occurring: manufacturing, business diversification, R&D competition, product development, innovation pattern, and societal diffusion of technology. He illuminates his discussion of each dimension with a profile of specific technologies and the companies that have advanced them, including consumer electronics (Sony Toshiba), fiber optic cables (Sumitomo Electric), computers and communications equipment (NEC), machine tools (Fanuc), and automobile parts (Honda, Toyota, Nissan).
Keywords: Technological innovations,Manufacturing industries,Đổi mới công nghệ,Sản xuất công nghiệp; Economic aspects,Technological innovations,Khía cạnh kinh tế,Đổi mới công nghệ; Japan,Japan,Nhật Bản,Nhật Bản